Respuesta :

Answer:

[tex]x_1=3+2\sqrt{6}[/tex]

[tex]x_2=3-2\sqrt{6}[/tex]

Step-by-step explanation

[tex]\rule{100mm}{0.5mm}[/tex]

                           [tex]x^2-6x=15[/tex]

[tex]x^2-6x+\left(\dfrac{6}{2}\right)^2-\left(\dfrac{6}{2}\right)^2=15[/tex]

                   [tex]x^2-6x+3^2=15+3^2[/tex]

                     [tex]x^2-6x+9=15+9[/tex]

                          [tex](x-3)^2=24[/tex]

                       [tex]\sqrt{(x-3)^2} =\sqrt{24}[/tex]

                              [tex]x-3=\pm2\sqrt{6}[/tex]

                                  [tex]\red{\boxed{x_1=3+2\sqrt{6}}}[/tex]

                                  [tex]\red{\boxed{x_2=3-2\sqrt{6}}}[/tex]                                

[tex]\rule {100mm}{0.5mm}[/tex]